TINJAUAN YURIDIS PENGANGKUTAN KAYU TANPA SURAT KETERANGAN SAH HASIL HUTAN KAYU - Fadhila; Irene Mariane (Reformasi Hukum Trisakti, 2022)
For a company involved in the transportation of forest products, the Certificate of Legality of Timber Forest Products (SKSHHK) is crucial. According to Law Number 18 of 2013 concerning the prevention and eradication of forest destruction, the problem is formulated as what permits must be obtained in carrying out a business of transporting timber forest products and what should be the procedure for carrying out a business of transporting timber forest products. The research methodology makes use of deductive reasoning, normative jurisprudence, secondary data, data collection with literature study, qualitative data analysis, and conclusion drawing. According to the Law on Prevention and Eradication of Forest Destruction, research findings, analyses, and conclusions are permits that must be held in order to conduct business and transport timber and forest products includes Timber Transportation Invoices Processed (FA-KO), Certificate of Timber Forest Products (SKSHHK), and Permits for Collection of Timber Forest Products (IPHHK). According to Decision Number 13/Pid.Sus/2018/PN.Rhl, the defendant violated Article 12 letter e and Article 83 paragraph 1 letter b of Law Number 18 of 2013 by transporting timber and forest goods without SKSHHK.